Dampak Penghapusan Desa Perdikan Tawangsari, Winong dan Majan Tahun 1900-1990: Studi Pemerintahan dan Kebudayaan - Muh. Fikri Haikal (Medan Resource Center, 2023)
The villages of Majan, Winong, and Tawangsari were designated as perdikan villages in the 18th century AD, granting full power to the perdikan village leader to govern the administration and social culture of the perdikan community. However, in 1979, their fiefdom status was abolished and their privileges were revoked. This research aims to explore the early history of these perdikan villages, the dynamics of the fief community, and the impact of the abolition of their fiefdom status. Historical research methods including heuristics, source verification, interpretation, and historiography were employed. The fief villages of Majan, Winong, and Tawangsari were identified by their special privileges and power to regulate village government, marriage, land tenure rights, and religious practices. The abolition of their fiefdom status resulted in changes to the village government, marriage, and land tenure rights. This research provides insight into the dynamics of perdikan villages and their identity, as well as the impact of changes to their status and privileges.